LTE Network Radio Planning - I. R. Maravić; A. M. Nešković (Telfor Journal, 2012)
In this paper different ways of planning the radio resources within an LTE network are analyzed. All simulations were carried out using 3GPP recommendations. Soft frequency reuse (SFR), soft fractional frequency reuse (SFFR) and hard fractional frequency reuse (HFFR) radio resource allocation schemes are compared to fixed frequency reuse 1 (R1) and reuse 3 (R3) radio resource allocation schemes. An optimum way of planning radio resources in a LTE network is proposed at the end of paper.